2016
DOI: 10.1075/lab.14013.deg
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of translation ambiguity

Abstract: Ambiguity in translation is highly prevalent, and has consequences for second-language learning and for bilingual lexical processing. To better understand this phenomenon, the current study compared the determinants of translation ambiguity across four sets of translation norms from English to Spanish, Dutch, German and Hebrew. The number of translations an English word received was correlated across these different languages, and was also correlated with the number of senses the word has in English, demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 28 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…First translational ambiguity is likely to occur in which more than one translation is possible for a given word [ 24 ], and this needs to be acknowledged and addressed by the bilingual committee. In some instances, we chose to provide more than one word in the translated document to make understanding clear.…”
Section: Discussionmentioning
confidence: 99%
“…First translational ambiguity is likely to occur in which more than one translation is possible for a given word [ 24 ], and this needs to be acknowledged and addressed by the bilingual committee. In some instances, we chose to provide more than one word in the translated document to make understanding clear.…”
Section: Discussionmentioning
confidence: 99%
“…author is hidden in the text), untranslatability (no same meaning as the original word is available in the translated language), and the translators, should be considered (Degani et al, 2016). The effect of the aforementioned factors was minimized by following a standard method of translation in the translation process.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, Tokowicz, Kroll, de Groot, and van Hell (Tokowicz et al 2002) conducted an analysis of stimuli use in previously published bilingual studies and observed that roughly a quarter of items used in these well-known studies had multiple translations. Since then, translation ambiguity has been explored in various paradigms and been manipulated in studies focused on language acquisition (Basnight-Brown and Altarriba 2016; Bracken et al 2016;Degani et al 2016;Tokowicz and Kroll 2007;Tseng et al 2014).…”
Section: Translation Differences In Multilingual Populationsmentioning
confidence: 99%